2020
DOI: 10.1080/21501203.2020.1752321
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and toxigenic potential ofAspergillussectionFlavion wheat and sorghum silages in Uruguay

Abstract: Species belonging to Aspergillus section Flavi occur naturally in crops and can cause food spoilage and/or toxin production. The aim of this study was to determine the occurrence and diversity of the species of Aspergillus section Flavi found in wheat and sorghum at harvest time and during silage storage, and to evaluate the toxigenic potential of the isolates to determine the contamination risk of mycotoxins in grains. Strains from Aspergillus flavus and Aspergillus parasiticus were found based on multi-gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…Aspergillus flavus is usually not an important field contaminant of wheat [ 136 , 137 , 138 ]. It can be problematic in storage [ 136 , 139 ], however, with the rate of contamination potentially increasing with time [ 140 , 141 ].…”
Section: Fungimentioning
confidence: 99%
“…Aspergillus flavus is usually not an important field contaminant of wheat [ 136 , 137 , 138 ]. It can be problematic in storage [ 136 , 139 ], however, with the rate of contamination potentially increasing with time [ 140 , 141 ].…”
Section: Fungimentioning
confidence: 99%
“…The fourth publication found AFB 1 (8%) and fumonisins (4%) in sorghum grains (n = 50) (García y . The fifth publication found 30% of AFs in 80 samples of wheat and sorghum grains (del Palacio and Pan, 2020). Finally, Capelli et al (2019) found AFM 1 in 91.8% of cow milk samples from 18 farms in the country.…”
Section: Uruguaymentioning
confidence: 97%
“…From a public health view and in regard to the SGM complex, A. flavus and its close relative within the Flavi section, A. parasiticus, are of the highest concern within the Aspergillus genus (Sarma et al, 2017). Compared to A. parasiticus, A. flavus has a wide host range, and is much more prevalent in the SGM complex across locations (Amaike and Keller, 2011;Little et al, 2011;Gemede and University, 2016;del Palacio and Pan, 2020). Out of the more than 20 known aflatoxins there are four major aflatoxins which are a focus of studies for their abundance in foods and toxicity: B1, B2, G1, G2, and M1 (Iqbal et al, 2015;Kumar et al, 2017).…”
Section: Aspergillus Sppmentioning
confidence: 99%